Using obsidian in glass art practice - Wadsworth, Fabian Ben; Llewellin, Edward; Rennie, Colin; Watkinson, Cate; Mitchell, Jo; Vasseur, Jeremie; Mackie, Alastair; Mackie, Fleur; Carr, Alexandra; Schmiedel, Tobias; Witcher, Taylor; Soldati, Arianna; et al. (Volcanica, 2022)
Glass art practice is indivisible from the material behaviour of glass at a range of working conditions, providing a direct link with the science of glass and melts. The use of non-standard, non-commercial, or natural glass compositions in art usually brings with it challenges associated with unexpected or undesirable processes, such as bubble formation and growth, liquid-liquid immiscibility, heterogeneities, and devitrification. For these reasons, natural geological compositions, including obsidian, have typically been avoided in glass art, with a few pioneering exceptions. Here, we bring together the results of mutual experimentation, knowledge-exchange workshops, and successful obsidian and magma use-cases in glass art in order to constrain the usability of obsidian and the techniques most suitable for rendering the material amenable to glass art practice. We conclude by exploring opportunities for collaboration between volcanologists and glass artists, which we propose would develop both fields in novel directions.